Fístula liquórica espontânea primária da base anterior do crânio: aspectos clínicos e fisiopatológicos - Alexandre Varella Giannetti (2009)
BACKGROUND AND PURPOSE: There has been an increase in the detection of primary spontaneous cerebrospinal fluid fistula (PSF) of the anterior skull base; however, many of its clinical, pathophysiological and therapeutical aspects are still misunderstood. The purpose of this paper was to evaluate such aspects. MATERIAL AND METHODS: Our study was made in two stages. In the first one, clinical data of 26 patients with PSF were compared to 23 patients with late traumatic fistula (LTF). Sex, age, location of the osteomeningeal breach, time of symptoms, number of episodes of meningitis, density of incidence of meningitis and final outcome were compared. In the second stage, a group of 20 patientswith PSF were compared to 20 normal control individuals in terms of skull base anatomy evaluated by computed tomography images. Skull base measurements and evaluation of the sphenoid sinus, position of the crista galli and status of the dorsum sella were made. Weight, height and body mass index (BMI) were also compared between these groups.RESULTS: In the first part of the study, female sex and sphenoid sinus location were more frequent in the PSF patients, whose mean age was 50 years. In the LTF group, male sex and fistula in the frontal and ethmoidal region were more common, while the mean age was 22 years. There were 0.6 and 1.3 episodes of meningitis per patient in the PSF and LTF groups, respectively (p=0.038). Density of incidence of meningitis was 0.1 and 0.2 per patient-month, in groups PSF and LTF, respectively (p=0.016). In the second part of the study, there was no difference in the diameters and angles of the skull base. Dorsum sella was founderoded in 30% of PSF patients and in none of the control group (p=0.020). Sellar height was larger in the PSF group (1.0 cm versus 0.8 cm, p= 0.002). All PSF patients were overweight and 50% were classified as obese. BMI in the PSF patients was higher than in control individuals (p=0.003). CONCLUSIONS: Presentation and epidemiological aspects differ in PSF and LTF patients. PSF patients had no global alterations in the skull base, though their increase in height of the sella turcica strengthens their association with empty sella syndrome. The erosion of dorsum sella found in PSF patients represents an indirect sign of intracranial hypertension.